The Economic Burden of Diabetic Retinopathy in Jordan: Cost Analysis and Associated Factors - Al-Dwairi RA; Aleshawi A; Abu-zreig L; Al-Shorman W; Al Beiruti S; Alshami AO; Allouh MZ (Dove Medical Press, 2024)
Rami A Al-Dwairi,1 Abdelwahab Aleshawi,1 Laith Abu-zreig,1 Wafa Al-Shorman,1 Seren Al Beiruti,1 Ali Omar Alshami,1 Mohammed Z Allouh2 1Department of Special Surgery, Division of Ophthalmology, Faculty of Medicine, Jordan University of Science & Technology, Irbid, 22110, Jordan; 2College of Medicine and Health Sciences, United Arab Emirates University, Al Ain, 15551, United Arab EmiratesCorrespondence: Rami A Al-Dwairi, Department of Special Surgery, Division of Ophthalmology, Faculty of Medicine Jordan University of Science and Technology, P. O. Box: 3030, Irbid, 22110, Jordan, Tel +962795355056, Fax +962 2 7201064, Email ramialdwairi@yahoo.com Mohammed Z Allouh, College of Medicine and Health Sciences, United Arab Emirates University, Al Ain, 15551, United Arab Emirates, Email m_allouh@uaeu.ac.aeObjective: Diabetic retinopathy (DR) is the leading cause of visual loss worldwide in patients with diabetes mellitus (DM). The aims of our study are to describe the costs associated with (DR) and to evaluate its economic impact in Jordan.Methods: Retrospectively, we included all patients with DM and classified them according to the severity of DR. Data regarding medical history, ophthalmic history, stage of DR, presence of DME, and the ophthalmic procedures and operations were collected. The total DR-related cost was measured as a direct medical cost for the outpatient and inpatient services.Results: Two hundred and twenty-nine patients were included in the study. Only 49.7% of the patients presented without DR, and 21% presented with diabetic macular edema (DME) unilaterally or bilaterally. The DR-related cost was significantly associated with insulin-based regimens, longer duration of DM, higher HbA1c levels, worse stage of DR at presentation, the presence of DME at presentation, the presence of glaucoma, and increased mean number of intravitreal injections, laser sessions, and surgical operations. Multivariate analysis should the presenting stage of DR, presence of DME, and the presence of DME be the independent factors affecting the DR-related cost.Conclusion: This study is the first study to be conducted in Jordan and encourages us to establish a screening program for DR for earlier detection and treatment. DM control and treatment compliance will reduce the heavy costs of the already exhausted healthcare and financial system.Keywords: diabetic retinopathy, economic burden, intravitreal injections, diabetic macular edema